Laminin-111: A Potential Therapeutic Agent for Duchenne Muscular Dystrophy - Goudenege, Sébastien (Nature Publishing Group, 2010)
Duchenne muscular dystrophy (DMD) still needs effective treatments, and myoblast transplantation (MT) is considered as an approach to repair damaged skeletal muscles. DMD is due to the complete loss of dystrophin from muscles. The lack of link between the contracting apparatus and the extracellular matrix leads to frequent damage to the sarcolemma triggering muscle fiber necrosis. Laminins are major proteins in the extracellular matrix. Laminin-111 is normally present in skeletal and cardiac muscles in mice and humans but only during embryonic development. In this study, we showed that intramuscular injection of laminin-111 increased muscle strength and resistance in mdx mice. We also used laminin-111 as a coadjuvant in MT, and we showed this protein decreased considerably the repetitive cycles of degeneration, inflammatory reaction, and regeneration. Moreover, MT is significantly improved. To explain the improvement, we confirmed with the same myoblast cell batch that laminin-111 improves proliferation and drastically increases migration in vitro. These results are extremely important because DMD could be treated only by the injection of a recombinant protein, a simple and safe therapy to prevent loss of muscle function. Moreover, the improvement in MT would be significant to treat the muscles of DMD patients who are already weak.